Penerapan Jaringan Wireless pada Desa Saentis Kabupaten Deli Serdang - Tengku Mohd. Diansyah; Ilham Faisal; Dodi Siregar (Universitas Harapan Medan, 2020)
Among the village administration, especially in Desa Saentis, the internet is a very important need in serving the community which is used as a medium for information exchange and direct communication with the community from a distance. However, the convenience of the internet is not really felt among the village government in the village of Percut Sei Tuan, apart from the internet network that is not supportive, the community service process is still completely manual, it is hoped that with a wireless network system connected to the internet it can serve the community through a website that will be provided by the government village. It is hoped that later the community around the Seantis Village Office can enjoy an internet connection and become an internet literate village and become a smart village with increasingly rapid technological developments. And the future benefit is that the village is expected to become a pilot village in Deli Serdang district by utilizing an internet connection to share information with the general public.